Analisis dan Perancangan Web Sistem Informasi Rental Mobil Pada LK Trans Jambi - Gusriyanti, Dwi Ayu (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Abstract− LK Trans Jambi, a car rental company in Jambi, faces challenges in operational efficiency and customer experience due to its still-manual system, where booking, verification, and transaction recording processes are time-consuming and prone to errors. This study aims to design a web-based information system using the prototype method to address these issues and enhance the company’s competitiveness. Utilizing Unified Modeling Language (UML) to model system requirements, the resulting prototype supports online booking, automatic data verification, and real-time vehicle availability tracking. The implementation of this system is expected to improve response times for customers, streamline operational management, and enhance internal and external communication, enabling LK Trans Jambi to deliver better services and remain competitive in the car rental market. Keywords: Design, System Information, Web, Prototype